Biofilm formation by the global outbreak strain of Mycobacterium chimaera results in significantly reduced efficacy of standard disinfectants - Oschmann-Kadenbach, Anna Maria; Konrat, Katharina; Schaudinn, Christoph; Sohl, Genevieve; Wagner, Dirk; Lewin, Astrid; Arvand, Mardjan (BMC microbiology, 2025)
In 2013, a global outbreak of Mycobacterium chimaera infections due to contaminated heater-cooler units emerged. This ongoing problem has highlighted the question of whether disinfection recommendations for medical devices containing water circuits are adequate for preventing contamination and possible recontamination by nontuberculous mycobacteria. The formation of biofilms in such devices exacerbates the problem. This study aimed to assess the efficacy of disinfectants on biofilms and suspensions of the M. chimaera strain ZUERICH-1, and to compare it with two unrelated M. chimaera strains obtained from different sources.
Gesehen am 19.02.2026